2020
DOI: 10.3390/ijms21155417
|View full text |Cite
|
Sign up to set email alerts
|

Application of Antibodies to Neuronally Expressed Nogo-A Increases Neuronal Survival and Neurite Outgrowth

Abstract: Nogo-A, a glycoprotein expressed in oligodendrocytes and central nervous system myelin, inhibits regeneration after injury. Antibodies against Nogo-A neutralize this inhibitory activity, improve locomotor recovery in spinal cord-injured adult mammals, and promote regrowth/sprouting/saving of damaged axons beyond the lesion site. Nogo-A is also expressed by neurons. Complete ablation of Nogo-A in all cell types expressing it has been found to lead to recovery in some studies but not in others. Neuronal ablation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Due to the beneficial effects of Nogo-A inactivation for the regeneration of injured nerve fibers [ 91 , 92 , 93 , 94 ], this molecule is the target in clinical trials aiming at the treatment of severe spinal cord lesions [ 72 ]. Antibodies or decoy receptors (‘Nogo-traps’) that block the function of Nogo-A could be tools of high potential for these therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the beneficial effects of Nogo-A inactivation for the regeneration of injured nerve fibers [ 91 , 92 , 93 , 94 ], this molecule is the target in clinical trials aiming at the treatment of severe spinal cord lesions [ 72 ]. Antibodies or decoy receptors (‘Nogo-traps’) that block the function of Nogo-A could be tools of high potential for these therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the beneficial effects of Nogo-A inactivation for the regeneration of injured nerve fibers 9194 , this molecule is the target in clinical trials aiming at the treatment of severe spinal cord lesions 72 . Antibodies or decoy receptors (‘Nogo-traps’) that block the function of Nogo-A could be tools of high potential for these therapies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported in previous study that Shenfu injection might show anti-inflammatory or anti-oxidative effects on myocardial ischemia-reperfusion injury, sepsis, and acute lung injury in rats [20][21][22][23]. Nogo-NgR was associated with axonal regeneration, and inhibition of Nogo-NgR could attenuate nerve injury in previous studies [24][25][26]. Results of our study indicated that Shenfu injection may suppress CA-induced Nogo-NgR up-expression in the hippocampus of rats and improve neurological function, which suggested that Shenfu injection might protect brain in rats with CA and be helpful for axonal regeneration through Nogo/NgR pathway.…”
Section: Discussionmentioning
confidence: 99%